Prevalence of anxiety and depression symptoms among handball players in Iceland and their attitude towards seeking psychological help - Sigrún María Jörundsdóttir 1993- (2017)
Anxiety and depression symptoms among athletes have been widely discussed over the past few years, but it seems like athletes hide their mental problems more than the average person. Recent research has shown that depression and anxiety symptoms are equally common among athletes and the general public. The purpose of the present research was to study the prevalence of depression and anxiety symptoms among handball players in the top and first division in Iceland, and the players’ attitude towards psychological help seeking. A survey was administered through social media were 254 players participated from 38 teams in the top and first division in Iceland both, males, and females. The results of this study showed that 56.4% of Icelandic handball players showed some symptoms of anxiety and 58.2% showed some symptoms of depression. In addition, 23.6% of the players had clinical anxiety symptoms and 17.9% had clinical depression symptoms. Despite the anxiety and depression symptoms among the players, only 5.7% used psychological help even though their attitude towards psychological seeking help was positive and there were approximately 81% who would use psychological service if it were available within their team. Keywords: mental health, athletes, handball players, anxiety, depression, injury, psychological help, help seeking, attitude Þunglyndis og kvíðaeinkenni meðal íþróttafólks hefur verið mikið til umræðu síðast liðin ár, en það virðist vera að það sé meiri leynd yfir einkennunum þegar fólk stundar íþróttir heldur en ekki. Rannsóknir hafa sýnt að einkennin eru alveg jafn algeng meðal íþróttafólks og almennings. Núverandi rannsókn var framkvæmd í þeim tilgangi að skoða algengi þunglyndis- og kvíðaeinkenni meðal handboltafólks í efstu og 1. deild á Íslandi og viðhorf leikmannanna til sálfræðiþjónustu. Lögð var fyrir könnun fyrir leikmenn í gegnum internetið og voru alls 254 leikmenn sem tóku þátt úr 38 liðum. Niðurstöður rannsóknarinnar sýndu að 56,4% sýndu einhver einkenni kvíða og að 58,2% sýndu einhver ...